Preliminaries drug-psychiatric study of Ayahuasca and its active ingredient - Ríos, Oscar (1962)
For the first time in Peru, a study of "ayahuasca" comprising folk, botanists and pharmacognostic aspects that are correlative and experimental testing of the pharmacodynamic and toxicological action of its active ingredient is made, prior recognition of chemical identity and one of its plant sources obtained in the Upper Ucayali. Such preliminary study is part of a strategy in the field of experimental psychiatry research today.